Electrocaloric effect in Sn substituted BaTiO3 ceramics: covering a broad temperature range. Issue 1 (16th May 2022) - Surampalli, Akash; Prajapat, Deepak; Reddy, V. Raghavendra
Abstract: The present work deals with the calculation of electrocaloric (EC) coefficients of BaTi1-x Snx O3 (x = 0.15, 0.20, 0.30) polycrystalline ceramics. Dielectric and polarization studies are carried out in a temperature range of 100 − 300 K to calculate the EC coefficients employing the indirect method based on Maxwell's equations. It is demonstrated that the EC effect is enhanced near the dielectric maxima for all the samples, including that of samples which exhibit relaxor behavior (x = 0.30). Furthermore, the maximum change in temperature, the temperature at which the maximum EC coefficient is achieved and the working range for EC effect are shown to be tunable with electric field and Sn substitution.